Synergistic impact of geopolymer binder and recycled coarse aggregates on the performance of concrete masonry units - Elen Abuowda; Hilal El-Hassan; Tamer El-Maaddawy (Cleaner Materials)
This study examines the combined effect of geopolymeric binder and recycled coarse aggregates (RCA) on the properties of concrete masonry units (CMU). A target 1-day compressive strength of at least 13.8 MPa was attained for all mixes to satisfy the load-bearing strength requirements. Geopolymer mixes made with RCA at replacement rates of up to 100 % were evaluated and compared to a cementitious control mix made with natural coarse aggregates. The environmental and economic impacts were then integrated with the quantity of waste valorized and compressive strength in a multifunctional performance index. Experimental results showed that the utilization of geopolymers as a substitute for Portland cement in the production of CMU did not impact the oven-dry density but reduced the water absorption capacity by up to 26 %. Although the incorporation of RCA negatively impacted these two properties, their values remained within the acceptable range stated by the standards. The geopolymer CMU mix made without RCA had 9 and 25 % lower 28-day compressive and splitting tensile strengths compared to the cement control mix, respectively. Subsequent RCA replacement further reduced these mechanical properties. While the linear drying shrinkage was reduced upon substituting the cementitious binder with the geopolymeric counterpart, RCA replacement of up to 100 % increased the linear drying shrinkage to reach 0.091 %, exceeding the limit set by the standard. Overall, the CMU mix made with geopolymer binder and 75–100 % RCA was found to be optimal for load-bearing applications.